Actors and roles in integration of electric vehicles in energy markets and power systems: Theory, glossary, and application to virtual power plant and fleet operator - Jan F. Heinekamp; Kai Strunz (International Journal of Electrical Power & Energy Systems)
Multilateral benefits for actors in the power system and energy market integration of electric vehicles (EVs) are crucial for a sustainable electrification of the transport sector. The overarching goal of this integration is to meet the EV energy demand at low cost for end users, while maximizing the use of renewable energy for charging. In liberalized energy markets, however, each actor may pursue own objectives depending on particular roles adopted. Regulatory frameworks specifying those roles are generally publicly available. Nevertheless, such frameworks are often complex and not easily accessible to stakeholders, creating barriers to market entry. Within this article, current legal and consolidated functional roles in liberalized energy markets are analyzed in the most comprehensive manner. All roles are categorized and respective relations are visualized for unparalleled insight, improving accessibility to stakeholders. A multi-actor market integration model is developed, accounting for regulatory framework conditions and ensuring transferability for real-world application. Important role distributions are simulated to illustrate multilateral benefits and facilitate policy decisions. The shown quantitative analysis of costs and revenues substantiates the importance of actor-specific modeling for accurate benefit allocation. It is demonstrated how virtual power plant operators as relevant actors make use of EV flexibilities in energy market trading combined with power purchase agreements for renewable energy. Emerging price benefits are shared with fleet operators. It becomes clear that the proposed methodology leverages the interactions and information exchange among involved actors, facilitating economic and ecological advantages in the integration of EVs into power systems and energy markets.